Analysis of spelling errors from the ‘dyslexic sight words’ list - Cidrim, Luciana; Batista, Andrea Oliveira; Madeiro, Francisco; Capellini, Simone Aparecida (Frontiers in Psychology, 2024)
In this study the spelling errors of the 'Dyslexic Sight Words' list are analyzed according to the semiological classification. The spelling errors were made by schoolchildren with and without dyslexia. The analysis by semiological classification provides explanations that can contribute to the teaching of Brazilian Portuguese orthography. The high number of inaccuracies by the Dyslexia Group is related to syllabic complexity and the psycholinguistic relevance of rule and orthographic irregularity. The reasons for the spelling disorders are mainly guided in two directions. The first concerns the difficulty that the written code brings in the face of irregularities in our language. The second refers to the relationship of this difficulty with failures in phonological, visual and orthographic working memory processing in dyslexics. In the teaching of spelling, success and error when writing should be followed by reflection (metaorthographic skill) and monitoring, both on the part of the teacher and on the part of the learner.The establishment of orthographic writing is a complex learning process and takes several years (Justi et al., 2020), because, in the writing of words whose orthographies demand more than the metaphonological skills, the mere exposure of the students to the written items (Cidrim et al., 2021) and the attempt to memorize orthographic rules are insufficient strategies to guarantee the reach of orthographic writing. This can be seen from research on orthographic processing (Apel et al., 2019), and the formal and explicit teaching of orthographic representations expected for the Portuguese language.It can be inferred that spelling knowledge is correlated with Orthographic Lexical